Iowa RBA, November 3, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for November 3, 1997. Highlights of the update include sightings of a White-winged Scoter, a Surf Scoter, a Pacific Loon, and the continued presence of a Lesser Black-backed Gull. Also of note were sightings of a White-winged Crossbill and a Red-necked Grebe as well as a report of 158 raptors observed on a hawk watch at Grammer Grove County Wildlife Area. Also included are handwritten notes for the next week's update with sightings of a Pine Grosbeak, a Bohemian Waxwing, and a Spotted Towhee. Epson - sheet feed